HDAC11 regulates interleukin-13 expression in CD4+ T cells in the heart. (September 2018) - Yuan, Li; Chen, Xiao; Cheng, Liang; Rao, Man; Chen, Kai; Zhang, Ningning; Meng, Jian; Li, Mengmeng; Yang, Li-Tao; Yang, Ping-Chang; Wang, Xin; Song, Jiangping
Abstract: Background and aims: Immune deregulation is a causative factor in pathogenesis of myocarditis. Histone deacetylases (HDAC) involve multiple biochemical activities in the cell. This study aims to elucidate the role of HDAC11 in the regulation of interleukin (IL)-13-expression in CD4 + T cells of heart tissue in patients with myocarditis (MCD). Methods: After heart transplantation, surgically removed hearts were collected from patients with advanced heart failure and MCD or dilated cardiomyopathy (DCM). CD4 + T cells were isolated from the heart samples and analyzed by immune assay. The association between IL-13 over production by CD4 + T cells in heart tissue and the pathogenesis of MCD was analyzed. Results: T helper (Th) 2-biased inflammation was observed in hearts tissue of MCD patients with advanced heart failure. CD4 + T cells isolated from MCD heart tissue showed lower levels of HDAC11 expression than that isolated from DCM heart tissue. HDAC11 was negatively correlated with IL-13 expression in the CD4 + T cells. A complex of HDAC11 and E4 binding protein-4 (E4BP4; the transcription factor of IL13 ) was detected in the CD4 + T cells, which restricted the binding between E4BP4 and the Il13 promoter to repress the Il13 gene transcription. Reconstitution of HDAC11 in MCD CD4 + T cells reduced the expression of IL-13, while inhibition of HDAC11 in DCM CD4 + T cells increased the IL-13 expression. Conclusions: HDAC11 is a regulatory molecule in Th2 response and plays a critical role in the restriction of the biased IL-13 expression in CD4 + T cells of the heart. Highlights: Th2-biased inflammation was observed in the hearts with myocarditis (MCD). CD4 + T cells of the MCD heart tissue had lower levels of HDAC11. HDAC11 restricted the expression of IL-13. Reconstitution of HDAC11 in the MCD CD4 + T cells reduced the expression of IL-13.